PENGARUH VISUAL AUDITORY KINESTETHIC TERHADAP KEMAMPUAN LOMPAT JANGKIT - Anggi Oktriadi; Andika Triansyah; Fitriana Puspa Hidasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe problem of this research is the lack of students' knowledge of athletic material. This research aims to find out whether there is an influence on the use of the Kinestethic Visual Auditory Approach of students’ triple jump ability. This research was conducted to the XII IPS students of Pontianak Islamiyah High School. The research method used is an experiment with the design of One Group Pre-test and Post-test. Sampling is done by using purposive sampling technique, namely the selection of samples with certain considerations. The sample was chosen based on the male gender of 16 students. Analysis of the data used in this study is t-test. The result of this research is the influence of the Visual Auditory Kinesthetic approach of students’ triple jump ability of class XII students based on the acquisition of t hitung > t tabel which is equal to 11.98> 1.7530 with an average difference at the time of the pre-test is 43.13 and the average value at the time of the post-test is 67.50. Thus the results of this research can be concluded that Ha = accepted and Ho = rejected. It means that there is an influence of the VAK approach to the ability of triple jump.Keywords: Athletic, Triple Jump, Visual Auditory Kinestethic